2009
DOI: 10.1587/elex.6.1582
|View full text |Cite
|
Sign up to set email alerts
|

Memory cell using Modified Field Effect Diode

Abstract: Using spice 9.3, we have modeled (I-V) characteristics of a Modified Field Effect Diode (M-FED) with gate length of 75 nm and oxide thickness of 10 nm. An SRAM cell (Register) has been designed with the simulated M-FED and has been compared to an SOI-MOSFET based circuit. Simulation results demonstrate that clock frequency applied to a memory cell which is designed with M-FED is more than 2 orders of magnitude larger than that of a comparable SOI-MOSFET, while the access time of the M-FED based memory cell is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…We have shown that field-effect diodes (FEDs) have superior characteristics over silicon-on-insulator metal-oxide-semiconductor field-effect transistors (SOI-MOSFETs) due to suppressed short-channel effects [2]- [4]. FEDs have been used for electrostatic-discharge protection [5]- [7] and memory-cell applications [8], [9].…”
Section: Performance Assessment Of Nanoscalementioning
confidence: 99%
“…We have shown that field-effect diodes (FEDs) have superior characteristics over silicon-on-insulator metal-oxide-semiconductor field-effect transistors (SOI-MOSFETs) due to suppressed short-channel effects [2]- [4]. FEDs have been used for electrostatic-discharge protection [5]- [7] and memory-cell applications [8], [9].…”
Section: Performance Assessment Of Nanoscalementioning
confidence: 99%
“…Among proposed alternative structures, modified Field Effect diode is introduced for high-performance and low-power applications [1,2,3,4,5,6,7,8].…”
Section: A Brief Of Nanoscale Field Effect Diodementioning
confidence: 99%
“…The nanoscale Field Effect Diode is considered one of the most promising structure to suppress the short channel effects for a given equivalent gate oxide thickness by using multiple gates to control the channel [1,2,3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the I ON /I OFF ratio, one of the most important parameters in digital applications, is more in this device than the field-effect transistors with similar dimensions [5,6]. The FEDs have different applications such as electrostatic discharge (ESD) [7,8] and memory cells [9][10][11], and also can be used to design integrated circuits [12][13][14]. The OFF-state current is an important parameter in the FEDs, therefore it is desirable to be as small as possible.…”
Section: Introductionmentioning
confidence: 99%